Democratic Republic of the Congo : First Review under the Extended Credit Facility Arrangement, Request for Modification of Performance Criteria, and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for the Democratic Republic of the Congo. (IMF Staff Country Reports; Country Report ;, 2022)
After a third wave over the summer, COVID-19 cases are declining but vaccination has stalled. Economic activity has improved on the back of strengthened external demand, allowing for a stronger-than-envisaged buildup in international reserves. Inflation and the exchange rate have stabilized. Near-term challenges arise from uncertainty related to the pandemic and the gradual global economic recovery supporting high commodity prices.